2002
DOI: 10.1051/forest:2001008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the dual arbuscular endomycorrhizal / ectomycorrhizal symbiosis on the growth of Acacia holosericea (A. Cunn. ex G. Don) in glasshouse conditions

Abstract: -Acacia holosericea plants were inoculated with a strain of Glomus aggregatum IR27 (arbuscular mycorrhizal fungus), Pisolithus tinctorius COI024 (ectomycorrhizal fungus) or with both fungi. Each fungus inoculated alone stimulated plant growth (height and shoot biomass). The response to the dual inoculation was greater than the response to either inoculant one. It may be due to the fact that the co-inoculated plants formed nodules through contaminations. However these nodules are inefficient as the N concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 19 publications
0
25
0
2
Order By: Relevance
“…However, some authors have found that in roots of some Acacia and Eucalyptus spp. both fungal symbionts can coexist without competition [18,27], what clearly shows that further analysis may be needed on this.…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors have found that in roots of some Acacia and Eucalyptus spp. both fungal symbionts can coexist without competition [18,27], what clearly shows that further analysis may be needed on this.…”
Section: Discussionmentioning
confidence: 99%
“…However, shoot P contents are significantly higher in AM than nonAM plants grown under both saline and nonsaline conditions, while shoot N and K contents were significantly higher in AM than non AM plants only under nonsaline and medium (SW1) saline conditions ( Table 4). The higher mineral nutrient uptake in AM compared to nonAM plants (higher contents of N, P and K) under saline conditions likely occurred because of improvement of soil exploration by mycorrhizal extraradical hyphae that extend beyond root depletion zone which resulted in reducing antagonistic effects of salinity on nutrients uptake [25,27]. Enhanced uptake of N, P and K by AM plants has been reported by many researchers for different vegetable crops grown under saline conditions [25,[27][28][29].…”
Section: Nutrient Uptakementioning
confidence: 99%
“…The higher mineral nutrient uptake in AM compared to nonAM plants (higher contents of N, P and K) under saline conditions likely occurred because of improvement of soil exploration by mycorrhizal extraradical hyphae that extend beyond root depletion zone which resulted in reducing antagonistic effects of salinity on nutrients uptake [25,27]. Enhanced uptake of N, P and K by AM plants has been reported by many researchers for different vegetable crops grown under saline conditions [25,[27][28][29]. Concentrations and contents of Na were significantly lower in the shoots of AM than nonAM pepper plants grown under both saline but not nonsaline conditions (Tables 3 and 4).…”
Section: Nutrient Uptakementioning
confidence: 99%
“…The access of the roots to the nutrients, especially phosphate, can be enhanced by the association with mycorrhizal fungi (AMF). Literature has been confirming that dual inoculation significantly increases not only dry weight, nitrogen and phosphorus content of the shoot, but also the height and diameter of trunk and reduces plant mortality index [4,15,20,[26][27][28]38]. This way such increase of the N and P concentration in the leaves increases the litter quality and improves the turnover and decomposition of the biomass which adds nutrients to soil and produces the soil organic matter (SOM).…”
Section: Introductionmentioning
confidence: 99%